2014
DOI: 10.1002/chem.201406031
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Synthesis of N‐Aryl Benzamides by Rhodium‐Catalyzed ortho‐Amidation and Decarboxylation of Benzoic Acids

Abstract: The rhodium-catalyzed amidation of substituted benzoic acids with isocyanates by directed CH functionalization followed by decarboxylation to afford the corresponding N-aryl benzamides is demonstrated, in which the carboxylate serves as a unique, removable directing group. Notably, less common meta-substituted N-aryl benzamides are generated readily from more accessible para- or ortho-substituted groups by employing this strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 128 publications
0
19
0
1
Order By: Relevance
“…117 Notably, this strategy demonstrates the synthetic utility of a removable carboxylic acid directing group that both initiates Rh(III)-catalyzed ortho C–H aminocarbonylation and subsequently undergoes decarboxylative cleavage. Out of a variety of alkali phosphonate salts that were examined, K 2 HPO 4 was identified to be optimal, and in the absence of this additive none of the desired product was obtained.…”
Section: Isocyanatesmentioning
confidence: 95%
“…117 Notably, this strategy demonstrates the synthetic utility of a removable carboxylic acid directing group that both initiates Rh(III)-catalyzed ortho C–H aminocarbonylation and subsequently undergoes decarboxylative cleavage. Out of a variety of alkali phosphonate salts that were examined, K 2 HPO 4 was identified to be optimal, and in the absence of this additive none of the desired product was obtained.…”
Section: Isocyanatesmentioning
confidence: 95%
“…[30] It is worth noting that, contrary to when employing the Rh(III) catalyst, 2-methoxybenzoic acid was found to be compatible in this catalytic system and provided the desired products in 33% yield. [31] During the course of our investigation on the cyclization of otoluic acid with phenylisocyanate, 3-methyl-N- Isolated yields.…”
Section: Synthesis Of N-substituted Phthalimides Via Tandem 12-additmentioning
confidence: 99%
“…The substrate scope is similar to the Rhcatalyzed reaction (Table 4). [31] Scheme 11. Conjugate addition of 2-phenylpyridine analogues to a,b-unsaturated carbonyl compounds.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…53 This method uses catalytic amounts of Cu 2 O to promote protodecarboxylation of the amidation product. However, the authors showed that in its absence the desired decarboxylated product is obtained and although lower yields were exhibited, this showed the ability of rhodium to promote protodecarboxylation.…”
mentioning
confidence: 99%